The field diary from the Alicia Model to design scientific infographics: A collaborative autoethnographic resource to guide information design - Luna-Gijón, Gerardo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This paper aboard a new infographic design model that combines information design with ethnography. The field diary allows collecting the experience of graphic designers who have followed the Alicia model to design scientific infographics. Through participative action research and design ethnography, journals represent a collaborative autoethnography where narrative intervenes; establishing qualitative categories, it has been performed an interpretative process from notes in the journals. Positive results have been collected about the efficiency of the model, it facilitates the infographics design experience and allows the development of design thinking in practitioners that make scientific infographics.